1999
DOI: 10.1046/j.1440-1819.1999.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Linear automatic detection of eye movements during the transition between wake and sleep

Abstract: Slow eye movement (SEM) are a sensitive indicator of lowered consciousness or drowsiness in man. A new computerized method for detection of SEM was introduced. A linear regression analysis was applied in each moving window for approximation to the tangent line on the electro-oculogram curve. The results revealed that SEM were more frequent and their duration was shorter at stage wake than at sleep stages 1 and 2. The method was practically suitable for objective detection and measurement of SEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Several studies have specifically investigated SEM detection to identify sleep onset automatically (Atienza et al. , 2004; Hiroshige, 1999; Magosso et al. , 2006; Suzuki et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have specifically investigated SEM detection to identify sleep onset automatically (Atienza et al. , 2004; Hiroshige, 1999; Magosso et al. , 2006; Suzuki et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have specifically investigated SEM detection to identify sleep onset automatically (Atienza et al, 2004;Hiroshige, 1999;Magosso et al, 2006;Suzuki et al, 2001;Va¨rri et al, 1996;Virkkala et al, 2007). Va¨rri et al (1996) proposed a SEM detection method using non-linear filtering techniques and applied it to EOG data measured during evening activities before going to bed.…”
Section: Introductionmentioning
confidence: 99%
“…However, VS has an inherent problem of individual bias. Although there have been several attempts at objective measurement of SEM and REM, there seems to be low agreement between quantitative scoring and VS. Hiroshige 1 recently developed a linear regression (LR) method for automatic detection of these movements and obtained high agreement with the results of VS. We have developed a template matching (TM) method for autodetection of these movements 2 . In the present study, we applied both methods to the same 20 min electro‐oculogram (EOG) data in the transition from wakefulness to sleep and compared the results with those from VS.…”
Section: Introductionmentioning
confidence: 82%
“…The LR was applied in each moving window for approximation to the tangent line on the EOG curve. 1 The TM used various templates of the altered sine waves. These were applied to the EOG curves, and the degree of similarity was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In sleep research field, there exist some methods, but these methods were are not satisfactory. In 1999, a linear regression method was used for the detection of SEM, and it was reported that the cycle length of SEM was shorter at stage wake than at sleep stages 1 and 2 [6]. In 2006, Elisa Magosso developed a wavelet based method, which was under the assumption that energy distribution was modified during SEM epochs according to the observation of experimental data [3].…”
Section: Introductionmentioning
confidence: 99%